Faktor - faktor yang Mempengaruhi Ketidakmerataan Jumlah Penduduk di Indonesia Menggunakan Analisis Faktor - Thesya Josevin Wardani; Arnellis Arnellis (Journal of Mathematics UNP, 2019)
Abstract – Indonesia is the most populous country in the world after China, India and the United States. But Indonesia's large population is not followed by an even distribution of the population. Concentration of the population which is mostly fixed in big cities that have negative impact on the environment and the emergence of various social problems. Therefore, an effort is needed to find out which factors influence the inequality of population in Indonesia. This research was conducted with aim to get the model of factor analysis and factors that influence the inequality of population of Indonesia. This type of research is applied research. The data used1 was obtained from the SUSENAS Indonesian Statistics Agency (BPS) program in 2017 which were analyzed using factor analysis. Based on the research1 results obtained models of factor analysis and four factors that affect the unequal population in Indonesia, namely facilities and infrastructuries factors, environmental and housing factors, population independence factor, and population birth factor. Keywords: Factor Analysis, Population Amount, Inequality Problems